PENGARUH SUMBER DAYA MANUSIA DAN MODAL TERHADAP PROSES PRODUKSI DI SCTV - Diajeng Reztrianti (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
One of the media in mass communication that has the greatest influence on the formation of public opinion is television. Television can provide a variety of information so that it can be used by the public in completing their knowledge. In order to present television programs that attract public interest, a good television program is needed to entertain the public. Factors that support this interesting television program are human resources, capital, and the production process.